2006
DOI: 10.1353/eas.2006.0002
|View full text |Cite
|
Sign up to set email alerts
|

Micro and Small Enterprises (MSEs) Finance in Ethiopia: Empirical Evidence

Abstract: This article seeks enhanced understanding of the dynamics of open innovation and knowledge appropriation in African settings. More specifically, the authors focus on innovation and appropriation dynamics in African micro and small enterprises (MSEs), which are key engines of productivity on the continent. The authors begin by providing an expansion of an emergent conceptual framework for understanding intersections between innovation, openness and knowledge appropriation in African small-enterprise settings. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…In Ethiopia, at the level of strategy and policy, these roles of MSEs have received recognition. They see as means of providing employment, alleviating poverty, ensuring food security, and private sector development (Gebrehiwot and Wolday, 2006). Zewde(2002) identified that the MSE sector characterized by a number of highly diversified activities, which can create job opportunity for a large segment of the population.…”
Section: Service Sector (Retailer Transport Hotel and Tourism Ict mentioning
confidence: 99%
“…In Ethiopia, at the level of strategy and policy, these roles of MSEs have received recognition. They see as means of providing employment, alleviating poverty, ensuring food security, and private sector development (Gebrehiwot and Wolday, 2006). Zewde(2002) identified that the MSE sector characterized by a number of highly diversified activities, which can create job opportunity for a large segment of the population.…”
Section: Service Sector (Retailer Transport Hotel and Tourism Ict mentioning
confidence: 99%
“…Micro-credit is the most well-known service provided by microfinance programmes in the BOP market. The most important aspect of MEs is credit [ 3 , 4 ]. According to the current literature [ 51 , 63 , 78 ], a suitable quantity of credit improves the performance of entrepreneurial activities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…MSEs growth, development, expansion, diversification and upgrade is not continuing much as expected. Gebrehiwot and Wolday (2006), who conducted their research on this subject in Ethiopia, stated that insufficient loan size, loan lengths that do not match with the gestation periods and cash flow patterns of borrowers" activities financed by the loan, disappointment to disburse timely, and the propensity of group collateral requirements are the difficulties of MSEs in growing and diversifying their enterprise. In addition to this, Mulu (2007), who conducted a study on selected businesses in six major zones administrations of Ethiopia, identified these difficulties.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…Studies decided that the problem of MSEs are access to working capital and extended term credit, loan size, insufficient infrastructure, high transactional cost, imperfect managerial and practical experts and marketing glitches (Hailay, 2003;Gebrehiwot and Wolday, 2006;World Bank, 2008). Many writers have concluded the above listed problems of MSEs, and are still upset on each idea.…”
Section: Statement Of the Problemmentioning
confidence: 99%